Juxtaposing Physical and Recreational Activities with Satisfaction with Life – A Case Study of Female Academics in Obafemi Awolowo University, Nigeria - Bamgbopa, Afolaremi Bamkole; Babalola, Adejoke Clara (European Scientific Journal, ESJ, 2021)
This study was designed to assess the level of involvement of female academics in physical and recreational activities. It determined the life satisfaction status of female academics. It also ascertained the influence of participation in physical and recreational activities on female academics’ satisfaction with life in Obafemi Awolowo University, Ile-Ife. The study adopted descriptive survey research design.The population of the study comprised all the 361 female academic staff members of all the 13 faculties in Obafemi Awolowo University Ile-Ile, Osun State, Nigeria. This study adopted primary data collection using well structured designed questionnaire. A sample of 182 respondents was selected using a simple random sampling technique, where 14 female lecturers were randomly selected from each of the 13 faculties with respect to their departments. A self-designed questionnaire was used to collect data. The results revealed that the female academics were passively involved in physical and recreational activities and that their participation in physical and recreational activities have influenced their satisfaction with life greatly. The study concluded that physical and recreational activities had significant positive influence on satisfaction with life in respect to the subjects of the study.